Acute and Long-Term Effects of LVAD Support on Right Ventricular Function in Children with Pediatric Pulsatile Ventricular Assist Devices. Issue 1 (January 2018) - Iacobelli, Roberta; Di Molfetta, Arianna; Brancaccio, Gianluca; Filippelli, Sergio; Morelli, Stefano; Natali, Benedetta; Toscano, Alessandra; Drago, Fabrizio; Amodeo, Antonio
Abstract : Right ventricular failure (RVF) is a significant issue when considering left ventricular assist device (LVAD) implantation in pediatrics. The aim of this study was to evaluate the effects of LVAD on right ventricular (RV) function in children. We retrospectively reviewed clinical and echocardiographic data of children who underwent Berlin Heart EXCOR LVAD focusing on RV function before and after implantation (1, 3, and 6 month follow-up). An isolated LVAD was used in 27 patients. Median age was 11 months (interquartile range [IQR]: 5–24 months), with a median weight of 6.3 kg (IQR: 5–9 kg). Median time on ventricular assist device (VAD) support was 147 days (IQR: 86–210 days). Twenty patients were successfully bridged to orthotopic heart transplantation (OHT) (74%), six patients died (22%), and also heart function recovered in one patient (4%). Before LVAD implantation, nine patients (33%) showed a RV fractional area change (RVFAC) less than or equal to 30%. After implantation, mean RVFAC increased up until the 3 month follow-up (43.13%; p = 0.033) and then slightly decreased. In a subgroup of 18 patients, the average strain value increased after the 1 month follow-up ( p = 0.022). Right ventricular failure developed in 33% of patients before the 1 month follow-up, and 7.4% experienced RVF at the 6 month follow-up. No patient required biventricular assist device (BiVAD). In our population, pulsatile-flow LVAD in children allows optimal RV decompression and function post-LVAD as measured by improvement in RV function at echo particularly at 1 and 3 month follow-up. At long-term follow-up, the beneficial effects of LVAD on RV function seem to be reduced as signs and symptoms of late RVF may develop in some patients despite LVAD support.